Toward Male Individualization with Rapidly Mutating Y‐Chromosomal Short Tandem Repeats. Issue 8 (14th July 2014) - Ballantyne, Kaye N.; Ralf, Arwin; Aboukhalid, Rachid; Achakzai, Niaz M.; Anjos, Maria J.; Ayub, Qasim; Balažic, Jože; Ballantyne, Jack; Ballard, David J.; Berger, Burkhard; Bobillo, Cecilia; Bouabdellah, Mehdi; et al.
<x xml:space="preserve">Abstract</x> The value of 13 rapidly‐mutating (RM) Y‐STRs for differentiating male individuals is investigated in 14, 644 related and unrelated men sampled from 111 worldwide populations. Over 99% of the 12, 272 unrelated men were completely individualized. Of the 2, 378 father‐son pairs, 27% were separated. Figure: blue lines represent Y‐STR haplotypes shared between population pairs in a subset of 7, 784 males from 65 populations. Almost all shared haplotypes defined by conventional 17 Yfiler Y‐STRs (above) are resolved with the 13 RM Y‐STRs (below). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>